Come in, number 9 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
ICT Update Print version, 8 pages, bi-monthly. Free. Subscribe at ICT Update office, at CTA address (see page 15) Electronic edition. Subscribe at ictupdate.cta.int